Genomes of coral dinoflagellate symbionts highlight evolutionary adaptations conducive to a symbiotic lifestyle - Aranda, Manuel; Li, Y.; Liew, Y. J.; Baumgarten, S.; Simakov, Oleg; Wilson, M. C.; Piel, Jörn; Ashoor, H.; Bougouffa, S.; Bajic, V. B.; Ryu, T.; Ravasi, T.; et al. (Scientific reports, 2016)
Despite half a century of research, the biology of dinoflagellates remains enigmatic: they defy many functional and genetic traits attributed to typical eukaryotic cells. Genomic approaches to study dinoflagellates are often stymied due to their large, multi-gigabase genomes. Members of the genus Symbiodinium are photosynthetic endosymbionts of stony corals that provide the foundation of coral reef ecosystems. Their smaller genome sizes provide an opportunity to interrogate evolution and functionality of dinoflagellate genomes and endosymbiosis. We sequenced the genome of the ancestral Symbiodinium microadriaticum and compared it to the genomes of the more derived Symbiodinium minutum and Symbiodinium kawagutii and eukaryote model systems as well as transcriptomes from other dinoflagellates. Comparative analyses of genome and transcriptome protein sets show that all dinoflagellates, not only Symbiodinium, possess significantly more transmembrane transporters involved in the exchange of amino acids, lipids, and glycerol than other eukaryotes. Importantly, we find that only Symbiodinium harbor an extensive transporter repertoire associated with the provisioning of carbon and nitrogen. Analyses of these transporters show species-specific expansions, which provides a genomic basis to explain differential compatibilities to an array of hosts and environments, and highlights the putative importance of gene duplications as an evolutionary mechanism in dinoflagellates and Symbiodinium.